Development of ciprofloxacin radiopharmaceutical formulation in single vial - Nurlaila Z; Maula Eka S; Eva Maria W (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2010)
Bacterial infection diseases is the greatest death causes in Indonesia. Detection of the deep-seated infection location caused by the gram positive and gram negative bacteries could be done with nuclear technique using 99mTc-ciprofloxacin radiopharmaceutical. In order to fulfill the necessity of this radiopharmaceutical, the development of formulation in single vial based on Sn(II) chloride and tartaric acid instead of Sn(II) tartrat has been carried out. The aim of this investigation is to obtained the optimum condition of 99mTc-ciprofloxacin preparation with maximum labelling efficiency. Several parameters influencing the labelling process of 99mTc-ciprofloxacin such as the amount of tartaric acid, pH of the reaction, the amount of Sn(II) ion as a reducing agent and the incubation time has been studied. The labelling efficiency and the radiochemical purity of 99mTc-ciprofloxacin were determined by double chromatography system using Whatman I/methyl ethyl keton to determine the free 99mTc-pertechnetate and ITLCSG/(ethanol:water:ammonia = 2:5:1) to separate the free 99mTc-reduced. The optimum preparation condition was obtained at pH = 2.95-3.20, 2 mg of ciprofloxacin, 0.06 µg of tartaric acid, 50 µg of SnCl22H2O and 15 minutes incubation time at room temperature, gave 90-93 % of labelling efficiency, in wchich was stable for 20 minutes at room temperature. Beside that, studies on the effect of Na99mTcO4 solution volume to the 99mTc-ciprofloxacin labelling efficiency was carried out. Labelling with up to 0.3 mL of Na99mTcO4 solution volume gave less than 90 % labelling efficiency.Key words: radiopharmaceutical, ciprofloxacin, 99mTc, single vial